2011
DOI: 10.1007/s12560-011-9066-5
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Detection of Human Norovirus from Produce Using SYBR Green I-based Real-time RT-PCR

Abstract: Several foodborne norovirus gastroenteritis outbreaks have been linked to fresh produce. Rapid and sensitive detection can help prevent the release of contaminated produce items in the market. The objectives of this study were to apply a relatively inexpensive SYBR Green I-based real-time RT-PCR assay for the rapid detection of human norovirus (NoV) GI and GII on the surfaces of lettuce, cherry tomatoes, and green onions. Each washed produce commodity (25 g) was spiked with serial dilutions of NoV GI and GII s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…This sensitivity was higher than the one described by Scipioni and co-workers ( 29 ), who obtained linearity in NoV amplification in human stool samples in the range of 5.8×10 6 to 5.8×10 11 copies. Similar results were also obtained by other authors ( 30 ), who developed a SYBR Green-based real-time RT-PCR for NoV detection in lettuce, cherry tomatoes, and green onions. Recently, Oshiki and co-workers developed a microfluidic nested PCR amplification method for NoV detection in oysters and found that the assay could detect 10 2 -10 5 copies/g digestive tissue ( 31 ).…”
Section: Discussionsupporting
confidence: 89%
“…This sensitivity was higher than the one described by Scipioni and co-workers ( 29 ), who obtained linearity in NoV amplification in human stool samples in the range of 5.8×10 6 to 5.8×10 11 copies. Similar results were also obtained by other authors ( 30 ), who developed a SYBR Green-based real-time RT-PCR for NoV detection in lettuce, cherry tomatoes, and green onions. Recently, Oshiki and co-workers developed a microfluidic nested PCR amplification method for NoV detection in oysters and found that the assay could detect 10 2 -10 5 copies/g digestive tissue ( 31 ).…”
Section: Discussionsupporting
confidence: 89%
“…Some researchers consider that lettuce have the highest adsorption capacity and the most favorable conditions for viral persistence because of the size and the wrinkled texture of its leaves, compared to other smooth, flat surfaces; while others suggest that capacity of lettuce leaf to protect the virus against desiccation is less than green onions or coarse surfaces like ham [17]. In our studies of norovirus GI and GII detection from deli meat, tomato and lettuce similar detection limits of 10 RT-PCRU/25 g were obtained while for green onion limit was 1 RT-PCRU/25g [18,19]. To conclude, viruses can survive on the surface of fresh produce once they have been harvested and remain infectious for several days or for up to 5 weeks during commercial and household storage [20].…”
Section: Transmission and Associated Foodssupporting
confidence: 59%
“…A total of 122 fecal specimens were collected and tested. The highest dilution of real-time RT-PCR to generate a positive cycle threshold (C t ) signal was one realtime RT-PCR unit (RT-qPCRU) [13]. C t values versus log 10 viral genomic copies linear standard curves were generated from a continuous 10-fold dilution (See Figure S3, Additional le 5).…”
Section: Source Of Hunovs Clinical Samples (Including Suspected Hunovs)mentioning
confidence: 99%
“…HuNoVs are highly-infectious, and infected patients can shed high titers of virus particles with strong resistance to the environmental factors [10,11]. As cell culturing in vitro is still immature to replicate HuNoVs effectively [12], the detection of the virus mainly depends on the molecular approaches such as RT-PCR and RT-qPCR [13,14]. These molecular approaches require specialized equipment, unique reagents, and signi cant time for sample preparation and assay execution, all of which make them impractical for either clinical use or on-site assays of eld samples requiring quick results.…”
Section: Introductionmentioning
confidence: 99%